High‐Throughput Screening and Hierarchical Topography‐Mediated Neural Differentiation of Mesenchymal Stem Cells. Issue 11 (4th May 2020) - Yang, Liangliang; Jurczak, Klaudia Malgorzata; Ge, Lu; van Rijn, Patrick
Abstract: Biophysical factors such as anisotropic topography composed of micro/nanosized structures are important for directing the fate of human bone marrow‐derived mesenchymal stem cells (hBM‐MSCs) and have been applied to neuronal differentiation. Via high‐throughput screening (HTS) methods based on topography gradients, the optimum topography is determined and translated toward a hierarchical architecture designed to mimic the nerve nano/microstructure. The polydimethylsiloxane (PDMS)‐based topography gradient with amplitudes ( A ) from 541 to 3073 nm and wavelengths ( W ) between 4 and 30 µm is developed and the fate commitment of MSC toward neuron lineage is investigated. The hierarchical structures, combining nano‐ and microtopography (W0.3/W26 parallel/perpendicular) are fabricated to explore the combined topography effects on neuron differentiation. From the immunofluorescent staining results (Tuj1 and MAP2), the substrate characterized by W : 26 µm; A : 2.9 µm shows highest potential for promoting neurogenesis. Furthermore, the hierarchical features (W0.3/W26 parallel) significantly enhance neural differentiation. The hBM‐MSCs on the hierarchical substrates exhibit a significantly lower percentage of nuclear Yes‐associated protein (YAP)/TAZ and weaker cell contractility indicating that the promoted neurogenesis is mediated by the cell tension and YAP/TAZ pathway. This research provides new insight into designing biomaterials for applications in neural tissue engineering and contributes to the understanding of topography‐mediated neuronal differentiation. Abstract : Topography‐mediated stem cell differentiation is tremendously impactful in directing and enhancing the differentiation toward the correct lineage. The magnitude of size possibilities along with the emergence of hierarchical structures makes it important to combine approaches such as high‐throughput screening and rational hierarchical substrate design as is illustrated here for enhance neuronal differentiation of mesenchymal stem cells.